Pengaruh Customer Engagement di Media Sosial terhadap Brand Intimacy pada Produk Fashion Lokal Indonesia - Nawastha, Classica Harsya; Alversia, Yeshika (UI Scholars Hub, 2020)
The fashion industry is one of the industries that is constantly expanding and Indonesia is the ninth largest contributor globally. Domestic growth of the fashion industry is supported by the campaign to love local products. Local fashion brands utilize the social media as a channel to communicate directly with their customers to develop a strong customer engagement. Therefore, it is important to know which factors influenced customer engagement, such as advice seeking, self image expression, and fashion involvement. Moreover, customer engagement also plays a role in the formation of brand intimacy. This study develops customer engagement as a second-order construct which consists of consumption, contribution, and creation. The survey was conducted online with 262 respondents which was then analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The findings show that advice seeking, self-image expression, and fashion involvement infuences customer engagement. Subsequently, customer engagement influences brand intimacy.